A Memory-Based Hysteresis Model in Piezoelectric Actuators - Guilin Zhang; Chengjin Zhang; Jason Gu (Journal of Control Science and Engineering)
A mathematical memory-based model is proposed to capture the hysteresis behavior in piezoelectric actuators. It is observed that the ascending (descending) hysteresis curves are alike and converge to one point without memory saturation. Therefore, two, dominant curves are determined and expressed as continuous functions, and the other hysteresis curves are modeled using two dominant curves through nonlinear transforming of coordinate axis. In the event of memory saturation, a new converging point is used to compensate the model prediction error. The experimental study has been carried out and our proposed model prediction method is compared with PI model and the linear model. It shows that the proposed model prediction method is better than other two methods.